Importance of Government Role in Export Credit Insurance System - Kanapėnaitė-Mažintienė, Aurelija (Ekonomika, 1999)
In recent years, however, a number of developments have occurred in the business and market environment that have deeply effected the role and functioning of export credit insurance agencies. Traditionally, the Government is involved in export credit insurance policy. This is partly due to the interlocking between export credit and export promotion policies, but also because, at least the government is considered the only institution in a position to bear the risk connected with export transactions. The export credit insurance system of Lithuania is still underdeveloped. Accordingly, government will need to take concrete steps to build on an efficient and effective supportive mechanism of export credit insurance. By covering exporters from commercial and political risks, the export credit insurance company reassures them that they will be paid and gives them the necessary confidence to export. Once the major risks associated with export transactions have been removed, exporters are able to concentrate on production, quality, marketing and other determinants.